The use of games in teaching vocabulary to young learners: a case study at Nguyen Binh Khiem primary school = việc sử dụng trò chơi trong dạy từ vựng cho trẻ em: nghiên cứu trường hợp tại trường tiểu học Nguyễn Bỉnh Khiêm - Nguyễn, Thị Kim Liên (2020)
No matter what language a child learns, it is words that serve as a stepping stone to the acquisition of language elements and skills. Among a handful of techniques in teaching and learning words, games are considered one of the best ones. The present study, therefore, aimed at investigating the current situation of applying games in teaching vocabulary to young learners by teachers of English at Nguyen Binh Khiem primary school. Specifically, it explored ways of using games, their effectiveness, practical issues and recommendations during the employment. Both qualitative and quantitative approaches, along with three research instruments namely observation, interview and testing, were adopted with the hope of giving in-depth answer to the four reseach questions. In addition to six observed lessons in two classes, two teachers of English were involved in the interview and 54 pupils were invited to do achievement tests. The results indicated that various games were exploited in all of three stages of vocabulary lessons, especially in practice and revision. Besides, with positive attitudes from teachers and pupils as well as pupils’ high scores in the tests, games were proved effective in helping children learn vocabulary, especially in terms of denotation and pronunciation. Challenges from pupils such as disruptive behaviors, unenthusiastic involvement and intense competition and issues from teachers like unclear instruction and neglect of scoring made it sometimes difficult for teachers to manage classes during games. However, these issues were addressed with solutions suggested by both teachers. Despite the researcher’s efforts, there were certain limitations such as the lack of pupils’ opinions and oral test and limited number of participants, which are hoped to be overcomed in future studies.